2010
DOI: 10.3171/2010.1.jns091169
|View full text |Cite
|
Sign up to set email alerts
|

Posterior interhemispheric transfalx transprecuneus approach to the atrium of the lateral ventricle: a cadaveric study

Abstract: Object The posterior interhemispheric transprecuneus gyrus approach is one of the surgical routes that has been suggested to reach the atrium of the lateral ventricle. It has the advantage of avoiding the disruption of the optic radiations; however, it has a narrow working area that at times makes the execution of this approach rather challenging. The aim of this study was to test a modification of the approach that might create a better surgical angle and a wider corridor by accessing the atrium from the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…This route is indicated for small or medium-size meningiomas with medial projection. The disadvantages are wider brain retraction is necessary, the narrow working angle, narrow surgical corridor and difficult access to the choroidal vessels 3,17,21 . We used this route in our case 6 with excellent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This route is indicated for small or medium-size meningiomas with medial projection. The disadvantages are wider brain retraction is necessary, the narrow working angle, narrow surgical corridor and difficult access to the choroidal vessels 3,17,21 . We used this route in our case 6 with excellent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Occipital lobe retraction may lead to postoperative visual field deficits, and entering the interhemispheric fissure as well as cutting the falx may jeopardise the integrity of the venous structures, including the venous sinuses and bridging veins [9]. By rotating the head so that the retracted hemisphere falls away from the falx, releasing CSF from the cistern of the great cerebral vein, and performing gentle manipulation during surgery, we have avoided postoperative visual field deficits due to occipital lobe retraction.…”
Section: Optic Radiation Preservation the Anatomical Study Conducted Bymentioning
confidence: 98%
“…Reduced retraction with improved exposure. Based on their anatomical study, Wang et al proved that the CITT approach can expose the trigone with a wider surgical angle compared with the conventional ipsilateral approach [9]. In the CITT approach, the patient is placed in a prone position, and the head is rotated such that the hemisphere harbouring the tumour is at a higher position [4].…”
Section: Optic Radiation Preservation the Anatomical Study Conducted Bymentioning
confidence: 99%
“…They suggested that this approach can expose the atrium and the posterior part of the temporal horn of the lateral ventricle with a wider surgical angle compared to the conventional homolateral posterior interhemispheric transprecuneus gyrus approach (36).…”
Section: A B C Dmentioning
confidence: 99%